2016
DOI: 10.1111/gcb.13477
|View full text |Cite
|
Sign up to set email alerts
|

Thermal limits of leaf metabolism across biomes

Abstract: High-temperature tolerance in plants is important in a warming world, with extreme heat waves predicted to increase in frequency and duration, potentially leading to lethal heating of leaves. Global patterns of high-temperature tolerance are documented in animals, but generally not in plants, limiting our ability to assess risks associated with climate warming. To assess whether there are global patterns in high-temperature tolerance of leaf metabolism, we quantified T (high temperature where minimal chlorophy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

34
316
7

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(357 citation statements)
references
References 92 publications
34
316
7
Order By: Relevance
“…Ghouil et al () showed that Quercus suber seedlings subjected to a range of growth temperatures (10 to 40 °C) in a growth cabinet exhibited acclimation of P HT , with T crit acclimating approximately 0.3 °C per °C increase in growth temperature (Ghouil et al, ). More recently, O'Sullivan et al () reported seasonal variations in T crit at two sites (temperate woodland and a tropical rainforest) in Australia (three species at each site) consistent with thermal acclimation patterns, with the seasonal adjustments being similar to the biome‐to‐biome patterns of T crit values measured in summer at each site. Similar results were recently reported by Sastry and Barua () assessing seasonal variations in P HT at a dry tropical forest in India.…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Ghouil et al () showed that Quercus suber seedlings subjected to a range of growth temperatures (10 to 40 °C) in a growth cabinet exhibited acclimation of P HT , with T crit acclimating approximately 0.3 °C per °C increase in growth temperature (Ghouil et al, ). More recently, O'Sullivan et al () reported seasonal variations in T crit at two sites (temperate woodland and a tropical rainforest) in Australia (three species at each site) consistent with thermal acclimation patterns, with the seasonal adjustments being similar to the biome‐to‐biome patterns of T crit values measured in summer at each site. Similar results were recently reported by Sastry and Barua () assessing seasonal variations in P HT at a dry tropical forest in India.…”
Section: Introductionmentioning
confidence: 78%
“…Quantification of the temperature response of F o (i.e., F o ‐T curves)—or similar methods that assess PSII functionality (e.g., temperature dependence of the maximum quantum yield of PSII of dark‐adapted leaves)—therefore provides insights into the heat sensitivity of PSII (Bilger, Schreiber, & Lange, ; Curtis, Gollan, Murray, & Leigh, ; Curtis, Knight, Petrou, & Leigh, ; Krause et al, ; Krause & Weis, ; Krause, Winter, Krause, & Virgo, ; Schreiber & Berry, ; Schreiber, Colbow, & Vidaver, ; Zhang, Poorter, Hao, & Cao, ). Using such approaches, advances have been made in our understanding of the physiological mechanisms (Hüve, Bichele, Rasulov, & Niinemets, ; Hüve, Bichele, Tobias, & Niinemets, ; Yamane, Kashino, Koike, & Satoh, ), broader ecological patterns, and significance of photosynthetic heat tolerance ( P HT ) (Curtis et al, ; Downton, Berry, & Seemann, ; Ghouil et al, ; Knight & Ackerly, ; Knight & Ackerly, ; Knight & Ackerly, ; Krause et al, ; O'Sullivan et al, ; Seemann, Downton, & Berry, ; Zhang et al, ). What is less clear, however, is the extent to which there are inherent differences in P HT among species adapted to contrasting habitats.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Krause et al , 2010, 2013), and as such these T Max values are likely to reflect absolute thermal limits. O’Sullivan et al (2017) recently showed that the maximum temperature of PSII integrity was higher in the tropics (50.8 °C) than in high latitudes (41.5 °C in Alaska), but so far there is no experimental confirmation that high growth temperature can increase heat tolerance markedly above ~51 °C (Krause et al , 2013), with the exception of CAM succulents (Krause et al , 2016). …”
Section: Discussionmentioning
confidence: 99%
“…during or following exposure to high temperature events Ball 1996a, 1996b), which can be driven, in some cases, by intraspecific variation within species (Drake et al 2015) or by environmental variation across species collection sites (Lewis et al 2011). The effects of eCO 2 on the heat or high-temperature stress tolerance of plants can act on several sites or processes within cells (Weis and Berry 1988;Murata et al 2007), which may help determine major distribution patterns (Osmond et al 1987;O'Sullivan et al 2017). Changes in A in response to eCO 2 can be related to membrane fatty acid saturation (Gombos et al 1994) or the activity of Rubisco (Law and Crafts-Brandner 1999;Salvucci and Crafts-Brandner 2004).…”
Section: Eco 2 and Heatwave Responsesmentioning
confidence: 99%